The study of lipid peroxidation and cytolytic processes after the administration of placenta cryoextract on the model of CCl4-induced hepatitis - Кошурба, І.В. (Матеріали Міжвузівської конференції «Медицина третього тисячоліття»; 2023 Лютий 13–15; Харків: Харківський національний медичний університет МОЗ України; 2023, с. 332–4., 2023)
The search for new strategies for the correction of exogenous toxic liver lesions is due to the steady increase in the incidence of hepatitis and cirrhosis among the working population, which is an important medical and social problem [3]. The aim is to determine the effect of cryopreserved placenta extract (CEP) on the state of the liver of rats with tetrachloromethane (CCl4)-induced damage by indicators of lipid peroxidation and markers of cytolysis. Materials and methods. Experimental studies were conduct on 28 male rats weighing 200–220 g, randomized into four groups: I – intact rats (n=7); II (control) – rats with model pathology (acute CCl4-induced hepatitis) without treatment (n=7); III – rats (n=7) with acute CCl4-induced hepatitis, which were injected with CEP (0.16 ml/kg of body weight [4, 5], intramuscularly; IV – rats (n=7) with acute CCl4-induced hepatitis, which were injected, which were injected with the reference drug silibor (50 mg/kg, intragastric). Acute CCl4-induced hepatitis was reproduced by intragastric administration of a 50.0% oil solution of CCl4 at a dose of 10 ml/kg body weight of the animal once, which caused acute fatty liver dystrophy [1, 2]. CEP was administered 1 time per day for 5 days before the administered of CCl4. Animals were removed from the experiment after 24 hours after the administered of CCl4. The research material was blood and liver homogenates. Liver tissue was perfused with a cold (+4°C) isotonic 1.15% KCl solution and homogenized in a buffer solution at a ratio of 1:10 (weight/volume: 250 mg + 2.25 ml of 1.15% KCl solution), obtaining a 10.0% homogenate in which the content of reactants with thiobarbituric acid (TBA-RP), superoxide dismutase (SOD) activity, alanine aminotransferase (AlAt), aspartate aminotransferase (AsAt) activity & γ-glutamyl transpeptidases (γ-GTP) according to standard methods. Results and discussion. The study showed that the content of TBA-RP in liver homogenates was lower (p<0.01) by 35.6% in rats that were prophylactically injected with CEP compared to rats with simulated CCl4-induced hepatitis without treatment (control group). An increase in the level of catalase (p=0.02) with the use of CEP was established by 33.8% and an increase in the activity of SOD (p<0.01) by 45.5% compared to the indicators of rats in the control group. The level of γ-HTP decreased by 37.8% compared to the rats with untreated CCl4-induced hepatitis. The evaluation of the effect of five-day prophylactic administration of CEP and silibor on the reproduction of CCl4-induced liver damage showed the ability of the cryoextract used in the study to more clearly level the cytolytic syndrome against the background of model acute toxic hepatitis compared to the herbal preparation silibor. Thus, it was established that the level of AlAt in the peripheral blood of rats with CCl4-induced hepatitis after the administered of CEP decreased statistically significantly (p<0.001) by 56.0%, while the administered of silibor led to a decrease in the same indicator (p<0.001) only by 32.0% relative to the indicators of rats in the control group. Similar changes were observed in the level of AsAt – against the background of the administered of CEP, the indicated indicator decreased (p<0.001) by 48.6%, while when using the herbal reference drug, the indicated indicator was lower (p<0.01) by 28 .6% relative to the indicators of rats with CCl4-induced hepatitis without treatment. The specified changes in the level of aminotransferases led to a more pronounced normalization of the value of the de-Ritis coefficient, which increased by 28.7% (р=0.07) against the background of the administered of СEP, while after the prophylactic administration of silibor the similar indicator increased (р=0.06) by 19.5% compared to the indicators of rats without treatment. Conclusions. Prophylactic five-day administration of CEP leads to the leveling of CCl4-induced lipid peroxidation activation and signs of cytolysis syndrome.
Кошурба ІВ. The study of lipid peroxidation and cytolytic processes after the administration of placenta cryoextract on the model of CCl4-induced hepatitis. Матеріали Міжвузівської конференції «Медицина третього тисячоліття»; 2023 Лютий 13–15; Харків: Харківський національний медичний університет МОЗ України; 2023, с. 332–334. DOI: https://doi.org/10.5281/zenodo.7694985
Keywords: cryopreserved placenta extract